(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Ge n d e r i n e q u a l i t i e s p e r s i s t i n t h e society, particularly in politics, and their underrepresentation is widely seen in higher level positions. The purpose of the study is to briefly examine broad causes, effect of women participation in politics and remedies for due representation. Through academic literature in the area of economics and political science with specific concern about gender inequalities and women’s underrepresentation in politics is globally realized. Further, extensive secondary tools applied to establish factors responsible for women’s underrepresentation, women positive effects in politics and an effective system for their redressal. It is observed that still a misconception existing in the society that women are incompetent to handle core areas of administration like finance, economic development, foreign affairs, defense, trade, and entrepreneurship with particular reference to political and government machinery where women allocate portfolios limited to women-only issues. It is seen that reserving seats for women in politics yield positive outcomes. Furthermore, even after quotas were discontinued, quotas improved perceptions about women as leaders, increased girls’ aspirations, and helped women get elected. In a true democracy, women’s political participation is a precondition for realizing gender equality. However, globally, less than 25 per cent of seats are represented by women in parliament and only 12 per cent of women occupy head of state positions. This disparity is also found in local government in various countries.